2009
DOI: 10.1007/s11207-009-9481-z
|View full text |Cite
|
Sign up to set email alerts
|

Space – Time Distribution of G-band and Ca ii H-line Intensity Oscillations in Hinode/SOT – FG Observations

Abstract: Abstract.We study the space-time distributions of intensity fluctuations in 2 -3 hour sequences of multispectral, high-resolution, high-cadence, broad-band filtergram images of the Sun made by the SOT-FG system aboard the Hinode spacecraft. In the frequency range 5.5 < f < 8.0 mHz both G-band and Ca II H-line oscillations are suppressed in the presence of magnetic fields, but the suppression disappears for f > 10 mHz.By looking at G-band frequencies above 10 mHz we find that the oscillatory power, both at thes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Lawrence & Cadavid [2010 and Chitta et al [2012a] were able to corroborate these general findings through examination of Hinode/SOT G-band image sequences containing MBPs. However, interestingly Chitta et al [2012a] found evidence to suggest that magnetoacoustic power at the highest temporal frequen-cies (i.e., periodicities less than 100 s) actually demonstrated power amplification.…”
Section: Magneto-acoustic Wavessupporting
confidence: 55%
See 1 more Smart Citation
“…Lawrence & Cadavid [2010 and Chitta et al [2012a] were able to corroborate these general findings through examination of Hinode/SOT G-band image sequences containing MBPs. However, interestingly Chitta et al [2012a] found evidence to suggest that magnetoacoustic power at the highest temporal frequen-cies (i.e., periodicities less than 100 s) actually demonstrated power amplification.…”
Section: Magneto-acoustic Wavessupporting
confidence: 55%
“…Through examination of the magneto-acoustic wave dynamics associated with large-scale sunspots, Nagashima et al [2007] employed Hinode/SOT observations to reveal how oscillatory power is often drastically reduced in the presence of strong magnetic field concentrations; a common phenomenon now referred to as 'acoustic power suppression' [e.g., Woods & Cram, 1981;Thomas et al, 1982;Title et al, 1992;Parchevsky & Kosovichev, 2007;Chou et al, 2009;Ilonidis & Zhao, 2011;Couvidat, 2013]. Lawrence & Cadavid [2010 and Chitta et al [2012a] were able to corroborate these general findings through examination of Hinode/SOT G-band image sequences containing MBPs. However, interestingly Chitta et al [2012a] found evidence to suggest that magnetoacoustic power at the highest temporal frequen-cies (i.e., periodicities less than 100 s) actually demonstrated power amplification.…”
Section: Magneto-acoustic Wavesmentioning
confidence: 99%
“…by Pietarila et al (2009), while the bandwidth of PK-027 data is close to that of the Ca II H high-resolution images, from the SOT/BFI instrument (Tsuneta et al 2008) onboard the Hinode spacecraft, studied e.g. by Lawrence & Cadavid (2010).…”
Section: Discussionmentioning
confidence: 67%
“…From their gradient, the corresponding phase velocities are calculated, assuming that the height separation between Ca ii H and G-band is 200 km (see text). power around magnetic concentrations in Ca ii H observations (Lawrence & Cadavid, 2010) shows that the magnetic canopy affects the oscillatory field in this bandpass and, therefore, the latter mechanism may also be in effect as well.…”
Section: Phase Differences Between Ca II H and G-bandmentioning
confidence: 87%
“…lower phase differences. The suppression of acoustic power around magnetic concentrations in Ca ii h observations (Lawrence & Cadavid 2010) shows that the magnetic canopy affects the oscillatory field in this bandpass and, therefore, the latter mechanism may also be in effect as well.…”
Section: Phase Differences Between Ca II H and G-bandmentioning
confidence: 92%